2017
DOI: 10.3389/fneur.2017.00162
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cells and Circadian Rhythms in Alzheimer’s Disease, Parkinson’s Disease, and Beyond

Abstract: There is increasing awareness on the role played by circadian rhythm abnormalities in neurodegenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The characterization of the circadian dysfunction parallels the mounting evidence that the hallmarks of neurodegeneration also affect the retina and frequently lead to loss of retinal ganglion cells (RGCs) and to different degrees of optic neuropathy. In the RGC population, there is the subgroup of cells intrinsically photosensitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 106 publications
(159 reference statements)
5
92
1
3
Order By: Relevance
“…Despite these differences between studies, further investigations of the eye in PD are desirable, given that it is known that ocular structures are involved in the pathology of several neurodegenerative diseases. 33,47 For example, tears, 48,49 lens, 50,51 cornea, 52 and retina 53 have already been investigated and proposed as sources for possible PD biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these differences between studies, further investigations of the eye in PD are desirable, given that it is known that ocular structures are involved in the pathology of several neurodegenerative diseases. 33,47 For example, tears, 48,49 lens, 50,51 cornea, 52 and retina 53 have already been investigated and proposed as sources for possible PD biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…Patients have a higher fragmentation, lower stability, lower amplitude, and lower mesor than healthy controls [40][41][42]. A low stability is also associated with poorer cognitive performance in Parkinson's disease [42].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…) as well as other sensory systems and motor function . In addition, sleep and circadian disturbances are a frequent complaint of PD patients associated with the eye, in particular the melanopsin‐containing RGCs, which are believed to control the circadian rhythm . In conclusion, visual complaints are common in PD patients, are likely to originate from a combination of retinal and (sub)cortical disease manifestations, and often affect activities of daily living (Table ).…”
Section: Abnormalities In Oculo‐visual Functionsmentioning
confidence: 99%
“…Delayed VEPs were demonstrated to correlate with severity of motor symptoms and disease duration, 33,126 whereas pattern ERG abnormalities correlated with clinical stage and disease duration and predicted reduced quality of life. 36,98,125 This led Garcia-Martin and colleagues 33 to conclude that pattern ERG may be used for detecting patients with a higher risk of progression. In addition, they and others have concluded that combining OCT and ERG/VEP biomarkers could increase diagnostic power and aid prediction of quality of life and disease severity.…”
Section: Electrophysiologymentioning
confidence: 99%